336SUPRASTERNAL APPROACH TAVR AVOIDS THORACOTOMY: FIRST IN MAN EXPERIENCE. (October 2014) - Kiser, A.C.; Stack, R.; O'Neill, W.; de Marchena, E.; Zarate, M.; Dager, A.; Reardon, M.
Abstract : Objectives: Direct aortic deployment of a transcatheter aortic valve eliminates the need to traverse the aortic arch with the valve delivery system, enables placement of large sheaths in the aorta and innominate artery, provides maximal precision during deployment, and ensures safe, conventional surgical aortotomy closure. We describe the initial experience with the Suprasternal Aortic Access System (SuprAA System, Aegis Surgical Ltd, Dublin, Ireland) for direct transaortic/innominate valve delivery. Methods: Patients with severe, symptomatic aortic stenosis who were candidates for TAVR via a direct transaortic approach were enrolled in the SuprAA-TAVR First-in-Man Study. Under general anaesthesia, the innominate artery and aortic arch were exposed in each patient using the SuprAA System via a 2.5-cm incision directly above the sternal notch. The TAVR delivery sheath was positioned and transcatheter valve deployed routinely under fluoroscopic guidance. Upon sheath removal, haemostasis at the aortotomy site was confidently secured using a double purse-string suture closure. All were extubated immediately. Results: Four male patients (mean age 82.5 years) underwent SuprAA-TAVR (2 CoreValve; 2 SAPIEN). Anatomical visualization was excellent and suprasternal valve deployment was accurate regardless of sheath size with 100% VARC-2 procedural success. The average total procedure time was 109.5 mins without perioperative wound or vascular complications. One patient required a pacemaker (Table 1 ). Conclusion: The SuprAA System provides direct aortic/innominate access without sternal or thoracotomy incision. Patient recovery to normal activity is maximized, sheath size limitations are eliminated and valve deployment is precise. This innovative system creates a new and exciting minimally invasive approach for high-risk patients with aortic stenosis.